Synthesis of cationic gold(III) complexes using iodine(III). Issue 8 (18th April 2019) - Albayer, Mohammad; Dutton, Jason L.
Abstract: We report the synthesis and characterization of cationic Au(III) complexes supported by nitrogen-based ligands. The syntheses are achieved by reacting Au(I) complexes [Au(N-Me-imidazole)2 ] + and [Au(pyridine)(NHC)] + with iodine(III) reagents PhI(OTf)(OAc) and [PhI(pyridine)2 ] 2+ yielding a series of cationic gold(III) complexes. In contrast, reactions of phosphine ligated gold(I) complexes with iodine(III) reagents results in the oxidation of the phosphine ligand. Abstract :